Ice friction in speed skating: can klapskates reduce ice frictional loss? - Houdijk, H.; Wijker, A. J.; de Koning, J. J.; Bobbert, M. F.; de Groot, G. (Medicine & Science in Sports & Exercise, 2001)
Purpose: Reducing ice friction was one of the motives for developing the klapskate. However, the magnitude of power dissipation that occurs with conventional skates when a skater plantar flexes his ankle and the tip of the blade is pressed into the ice has not been quantified previously. In this study, we examine how ice friction varies during a single stroke with conventional skates and estimate the reduction in ice friction that might be obtained with klapskates. Methods: Five elite speed skaters performed a series of trials at constant velocity and a series of maximal accelerations. Energy dissipated to ice friction during a stroke with conventional skates was analyzed using an instrumented skate and high-speed 3D kinematic analysis. The energy that would be dissipated when klapskates were used was estimated from the collected data with conventional skates. Results: The estimated difference in power loss between conventional and klapskates was less dramatic than has been suggested frequently. Pressing the tip of the blade into the ice comprises only 0.84 W of the total power dissipated by ice friction (54 W) during constant velocity speed skating. During an all-out acceleration, this power loss reached 4.55 W. Conclusion: We conclude that only a minor part of the benefit of klapskates can be attributed to a reduction in ice friction. It is shown that this relatively small increase in ice friction is related to the large length of the skate blade.